Wartime sexual violence at the international level: a legal perspective - Ward Arrabal, Caterina E. (International humanitarian law series, 2018)
In 'Wartime Sexual Violence at the International Level: A Legal Perspective' Caterina Arrabal Ward discusses an understanding of wartime sexual violence by the international tribunals and argues that wartime sexual violence often takes place without the explicit purpose to destroy a community or population and is not necessarily a strategic choice. This research suggests that a more focused approach based on a much clearer definition of these crimes would help to remedy deficiencies at the different stages of international justice in relation to these crimes